Análisis de la incidencia de los programas de estética en la construcción de estereotipos sobre la imagen personal en las universitarias de 18 a 30 años - Briones Ureta, María Deysi (2017)
Approximately 10 years ago we can observe the advertising and marketing of plastic surgery in Ecuadorian television in a television format, which is why this study seeks to identify the influence of these programs on the psychological and physical aspects of women. This project contains three chapters where an exhaustive analysis was made, which has been possible thanks to useful tools in the research and development of approaches; Interview and survey…….